MOS device chemical response reversal with temperature - Lombardi, Rina (2010)
Biased above threshold (VT), pulsed photocurrent (u) measurements on windowed silicon Pd gate MOS capacitors are shifted (ΔV) negatively by H2/N2, whereas Au gates shift positively under NO2/air. Below VT, the shifts are reversed by adjustments of interface state population. Minor temperature increases may coax the device from inversion to depletion, inducing sign reversal of the chemical response.